ASTM designation D820-93 : Standard test methods for chemical analysis of soaps containing synthetic detergents. (West Conshohocken (Pa.) : ASTM International)
1.1 These test methods cover procedures for the chemical analysis of soaps containing synthetic detergents. 1.2 The analytical procedures appear in the following order: Sections Moisture and Other Matter Volatile at 105[deg]C (Oven Method) 5 and 6 Free Alkali or Free Acid 7 and 8 Anhydrous, Salt-Free, Soda Soap 9 and 12 Alcohol-Soluble Matter 13 and 14 Matter Insoluble in Water 15 Total Alkalinity of Matter Insoluble in Alcohol (Alkaline Salts) 16 and 17 Sodium Silicate 18 to 20 Phosphates 21 to 28 Phosphate (Colorimetric Method Using Molybdenum Blue) 29 to 34 Unsaponified and Unsaponifiable Matter 35 to 39 Free Fatty Matter 40 Chlorides in Alcohol-Soluble Matter 41 to 43 Rosin (McNicoll Method) 44 to 47 Synthetic Detergent (by Difference) 48 Neutral Inorganic Salts 49
Keywords: Normen